An Opioid Overdose Curriculum for Medical Residents: Impact on Naloxone Prescribing, Knowledge, and Attitudes. Issue 3 (July 2018) - Taylor, Jessica L.; Rapoport, Alison B.; Rowley, Christopher F.; Mukamal, Kenneth J.; Stead, Wendy
Background : Despite escalating opioid overdose death rates, addiction medicine is underrepresented in residency curricula. Providing naloxone to at-risk patients, relatives, and first responders reduces overdose deaths, but rates of naloxone prescribing remain low. The goal of this study is to examine the impact of a brief curricular intervention for internal medicine residents on naloxone prescribing rates, knowledge, and attitudes. Methods : Internal medicine residents ( N = 160) at an urban, tertiary care medical center received two 1-hour didactic sessions addressing overdose prevention, including intranasal naloxone. The number of naloxone prescriptions generated by residents was compared to faculty, who received no similar intervention, in the 3-month periods before and after the curriculum. Resident knowledge and attitudes, as assessed by pre- and post-intervention surveys, were compared. Results : The resident naloxone prescribing rate increased from 420 to 1270 per 100, 000 inpatient discharges ( P = .01) and from 0 to 370 per 100, 000 ambulatory visits ( P < .001) post-intervention. Similar increases were not observed among inpatient faculty, whose prescribing rate decreased from 1150 to 880 per 100, 000 discharges ( P = .08), or among outpatient faculty, whose rate increased from 30 to 180 per 100, 000 ambulatory visits ( P < .001) but was lower than the post-intervention resident rate ( P = .01). Residents demonstrated high baseline knowledge about naloxone, but just 13% agreed that they were adequately trained to prescribe pre-intervention. Post-intervention, residents were more likely to agree that they were adequately trained to prescribe (Likert mean 2.5 vs. 3.9, P < .001), to agree that treating addiction is rewarding (Likert mean 2.9 vs. 3.3, P = .03), and to attain a perfect score on the knowledge composite (57% vs. 33%, P = .05). Conclusions : A brief curricular intervention improved resident knowledge and attitudes regarding intranasal naloxone for opioid overdose reversal and significantly increased prescribing rates.